2014
DOI: 10.1073/pnas.1323995111
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the homogenization of urban land management with an application to US residential lawn care

Abstract: Changes in land use, land cover, and land management present some of the greatest potential global environmental challenges of the 21st century. Urbanization, one of the principal drivers of these transformations, is commonly thought to be generating land changes that are increasingly similar. An implication of this multiscale homogenization hypothesis is that the ecosystem structure and function and human behaviors associated with urbanization should be more similar in certain kinds of urbanized locations acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(95 citation statements)
references
References 39 publications
8
87
0
Order By: Relevance
“…This variation, however, is only about 10% of the variation in studied urban sites (>12 kg C m À2 yr À1 ). Some studies have suggested that urbanisation reduces natural variability and has a homogenising effect on ecology as a result of similar land use, land management and species selection across the globe (McKinney, 2006;Groffman et al, 2014;Polsky et al, 2014).…”
Section: Annual Totals and Inter-annual Variabilitymentioning
confidence: 99%
“…This variation, however, is only about 10% of the variation in studied urban sites (>12 kg C m À2 yr À1 ). Some studies have suggested that urbanisation reduces natural variability and has a homogenising effect on ecology as a result of similar land use, land management and species selection across the globe (McKinney, 2006;Groffman et al, 2014;Polsky et al, 2014).…”
Section: Annual Totals and Inter-annual Variabilitymentioning
confidence: 99%
“…Since the Industrial Revolution, people's approaches to production and lifestyles have further encroached on all aspects of the traditional urban space; thus creating the so called "lost space" [4]. On one hand, people spend more time and money on meaningless commuting [5], which contributes to environmental deterioration and consumes energy [6]; on the other hand, urban space has gradually become occupied by motor traffic-and urban life has been relegated to the sides of the roads [7]. Since the 1960s, scholars have paid more attention to optimizing urban spaces and promoting outdoor activities [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of urban ecology theory, this raises the question of whether persistence in mesic lots indicates a maladaptive but path dependent system, much in line with field studies of lawn management and residential landscape preferences (e.g. Polsky et al, 2014). The failure of foreclosure to modify vegetation in a universal and detectable way suggests that many of the institutions that work beyond the household may play a strong and disparate role in modulating the degree to which foreclosure results in ecological change.…”
Section: Discussionmentioning
confidence: 92%
“…The failure of foreclosure to modify vegetation in a universal and detectable way suggests that many of the institutions that work beyond the household may play a strong and disparate role in modulating the degree to which foreclosure results in ecological change. This suggests that foreclosure, a temporally and spatially explicit opportunity for management change, may provide a useful experiment for the emerging ecological homogenization hypothesis, that surmises that cities are becoming more ecological similar to one another over time (Polsky et al, 2014). For instance, homeowner's associations are very common in Maricopa County (Turner & Ibes, 2011), may suppress the impact of foreclosure on yard vegetation when foreclosure are low and the income base for property management provided by other residents allows it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation